2011
DOI: 10.2135/cropsci2010.08.0478
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymorphisms at Bermudagrass Microsatellite Loci and Their Use in Genotype Fingerprinting

Abstract: The turf-type bermudagrasses include diploid Cynodon transvaalensis Burtt Davy, tetraploid C. dactylon (L.) Pers., and sterile triploid hybrids produced by crosses of these species. The objective of thiis study was to develop a set of mierosatellite markers that could distinguish among commercially important turf-type cultivars. A genomic library enriched for tfie [CA/GT]^ repeat motif was constructed from DNA of the Tifway' fiybrid and sequenced to identify mierosatellite regions. Twenty-five microsatellite-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…Harris-Shultz et al (2011) reported that the polymorphic fragment amplified by the Chase 109 primer was approximately 142 base pairs larger than the fragment length reported by Kamps et al (2011). Kamps et al (2011) suggested that microsatellite instability in plant tissues may be affected by irradiation, similar to mammalian tumors (Haines et al 2010), potentially explaining why TifEagle is distinguishable from Tifgreen-derived cultivars using the Chase 109 primer. This hypothesis is logical considering that TifEagle has been reported to be a mutant derived from an irradiated Tifway II rhizome (Hanna and Elsner 1999).…”
Section: Genetic Diversity Among Bermudagrass Cultivars Used On Puttimentioning
confidence: 85%
See 4 more Smart Citations
“…Harris-Shultz et al (2011) reported that the polymorphic fragment amplified by the Chase 109 primer was approximately 142 base pairs larger than the fragment length reported by Kamps et al (2011). Kamps et al (2011) suggested that microsatellite instability in plant tissues may be affected by irradiation, similar to mammalian tumors (Haines et al 2010), potentially explaining why TifEagle is distinguishable from Tifgreen-derived cultivars using the Chase 109 primer. This hypothesis is logical considering that TifEagle has been reported to be a mutant derived from an irradiated Tifway II rhizome (Hanna and Elsner 1999).…”
Section: Genetic Diversity Among Bermudagrass Cultivars Used On Puttimentioning
confidence: 85%
“…2). Kamps et al (2011) also failed to differentiate Tifgreen, Tifdwarf, Champion Dwarf, Floradwarf, or MS-Supreme using SSR markers.
Fig. 2Dendrograms display the genetic relationships among hybrid bermudagrasses ( Cynodon dactylon (L.) Pers.
…”
Section: Genetic Diversity Among Bermudagrass Cultivars Used On Puttimentioning
confidence: 99%
See 3 more Smart Citations